THE PERFORMANCE ANALYSIS OF RELIZATION AND BUDGET DISTRICT GOVERNMENT AREA SHOPPING SUMENEP 2014-2018: Analisis Kinerja Realisasi Anggaran Pendapatan Dan Belanja Daerah Pemerintah Kabupaten Sumenep Tahun 2014-2018 - Asnanur Faizah Asnanur Faizah; Mohammad Ghofirin (Universitas Nahdlatul Ulama Surabaya, 2020)
The study aims to analyze the performance of the realization of the regional income and expenditure budget of Sumenep Regency in 2014-2018. The data used in this study is secondary data, taken from the 2014 to 2018 annual fianancial reports from the Sumenep Regency APBD. The method used in this research is a qualitative descriptive analysis based on the Budget Realization Report (LRA), namely with the concept of a budget, espacially expenditure analysis. The results of this study, namely spending on LRA for 2014-208 show that the performance of Sumenep Regency Government spending is considered good and continues to make improvements every year in the utilization of spending realization. Expenditure growth began to appear in 2016 compared to 2014-2015. So that it is hoped that in the following year the Sumenep Regency Government should allocate a balanced portion of the region according to the needs of regional development and the welfare of the community. Allocation of regional expenditure so as to increase the effectiveness, productivity and efficiency of spending in the future.